PREMARRIAGE SEX EDUCATION IN AN EFFORT TO INCREASE KNOWLEDGE OF RISK SEXUAL BEHAVIOR IN ADOLESCENTS - Sena Wahyu Purwanza; Irma Wulandari; Kurniawan Erman Wicaksono; Dea Adesti Enofani (Universitas Airlangga, 2022)
Introduction: Risky sexual behavior in adolescents is a problem that is often experienced by most teenagers in Indonesia. The incidence of deviant behavior is currently increasing among adolescents. One example of cases of deviant behavior in adolescents is pregnancy outside of marriage. Therefore, it is necessary to have prevention activities by conducting socialization and health education related to risky sexual behavior in adolescents. Sexual education aims to help adolescents in making decisions and the risks of their sexual attitudes. The purpose of this community service activity is to increase adolescent knowledge regarding risky sexual behavior that often occurs in adolescents. Methods: The population of this activity is in the form of Health Education which is carried out on 320 students of class XI Vocational High School 10 Malang. The sample used in this activity is 10% of the total 32 students. The variable measured in this activity is adolescents' knowledge regarding risky sexual behavior. Health education activities began by conducting a pre-test using a questionnaire on risky sexual behavior in adolescents, then providing education with the lecture method and playing a video on the impact of sexual behavior on adolescents, and ending with a question-and-answer session accompanied by a post-test. Knowledge measurement is done by using univariate analysis by analyzing the results of pre and post-test. Results: The results of this activity can be seen from the post-test to pre-test results that have been carried out, namely an increase in student knowledge marked by a change in the score on five of the six achievement indicators. The first indicator is causes of free sex with an increase of 3.6%. The second indicator of the form of sex increased by 50%. Third, parties affected by premarital sex increased by 53.6%. Fourth, the purpose of premarital sex health education increased by 39.7%, and lastly, the prevention of premarital sex increased by 7.1%. With the results obtained an increase in the score indicates that the information conveyed by the researcher can be accepted by students well. Conclusion: The level of students' knowledge about premarital sex increased marked by a change in the score for the better on five indicators, namely knowledge related to causes, forms, affected parties, goals and prevention of premarital sex in adolescents. Health education needs to be carried out continuously, so that information related to good sexual education can be well absorbed by adolescents.